To save a life [videorecording (DVD)] - Wayne, Randy, 1981-; Kreutzberg, Deja, 1982-; Weigel, Joshua; Bailey, Robert, Jr; Lewis, Bubba, 1989-; Hidalgo, Kim; Morin, D. David (Sony Pictures Home Entertainment, 2010)
High school all-star Jake Taylor has it all. Roger, his childhood best-friend, has nothing. Since the two have drifted apart, Roger feels that he has no friends, no hope, and a heart full of nothing but pain. When Roger walks onto campus with a gun, the tragic move he makes will change Jake's idyllic life forever.